Preferensi Konsumen Terhadap Pembelian Buah Alpukat (Persea Americana Mill) Di Pasar Wisata Tawangmangu Kabupaten Karanganyar - Yulianti, Aisyah; Dewati, Rosita; Harinta, Yos Wahyu (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This study aims to determine the level of attributes that are most considered by consumers in purchasing decisions for avocados in the Tawangmangu tourism market. The basic method of this research uses descriptive analytic method and implements survey techniques. The research location was chosen purposively, namely the Tawangmangu tourism market. Determination of the sample using a purposive sampling method with a total of 60 respondents. The testing technique was carried out using the Fishbein Multi-attribute model. The results of this study indicate that the characteristics of consumers who buy avocados at the Tawangmangu tourism market are women aged 17-64 years with an average last education of S1/D4 of 35% with jobs/status as private employees earning an average income of Rp. 2,000,001-3,000,000, the average number of family members is 3-4 people in one house, with different regional origins which means that they are not only from Karanganyar Regency but consumers from Karanganyar Regency are the largest with 45%. The attitude of consumers towards the attributes of avocados that are most considered in purchasing decisions for avocados at the Tawangmangu tourism market is the taste of the fruit. Then the order of attributes that are most considered in purchasing decisions for avocados are taste attributes, fruit maturity level, fruit type, fruit price, fruit skin color and fruit size.